Placebo- and Nocebo-Effects in Cognitive Neuroenhancement: When Expectation Shapes Perception - Winkler, Alexander; Hermann, Christiane (Frontiers in Psychiatry, 2019)
Objective: The number of students using prescription drugs to improve cognitive performance has increased within the last years. There is first evidence, that the expectation to receive a performance-enhancing drug alone can result in improved perceived and actual cognitive performance, suggesting a substantial placebo effect. In addition, expecting a placebo can result in lower perceived and actual cognitive performance, suggesting a nocebo effect. Yet, the underlying mechanisms of these effects remain to be elucidated. The aim of our study was to investigate whether the expectation of receiving a performance-increasing drug or a performance-impairing drug leads to changes in actual and perceived cognitive performance, compared to a control group without expectation manipulation. Methods: A total of N = 75 healthy adults were recruited for an experiment to “try cognitive performance-modulating drugs”. Participant’s actual cognitive performance (alertness, working memory, sustained attention, and divided attention) using the standardized test of attentional performance (TAP) as well as their performance expectation were assessed. Participants were randomly assigned in equal numbers to either receiving a placebo performance increasing nasal spray (“Modafinil”) or a nocebo performance impairing nasal spray (“Vividrin®”) or no nasal spray (natural history). After placebo-/nocebo nasal spray administration, cognitive performance was re-assessed. Subsequent to the second assessment, participants rated their perceived change in cognitive performance, as well as adverse symptoms. Results: Unlike hypothesized, a positive or negative performance expectation did not result in changes in actual performance, corresponding to the induced expectation. Participants in the placebo-Modafinil group rated their perceived change in cognitive performance subsequent to the application of the nasal spray significant better (d = 1.16) compared to the nocebo- Vividrin® group. Additionally, participants who expected to receive Modafinil felt less tired than participants in the Vividrin® group (d = 0.96). Conclusion: Manipulation of performance expectation affects the perceived change in performance and tiredness, but not the actual cognitive performance in healthy adults. This may explain why college students use such drugs despite their little impact on actual cognitive functioning.